DECOMPOSITION OF LAMA GLAMA L. DUNG IN MEDITERRANEAN CLIMATE (Acta Entomológica Chilena, 2022)
The present paper deais with the decomposidon of Lama gluma dung and with the succession of theassociated soil micro-arthropods, in mediterranean climate of Chile.The numbers of species and individuáis of Acari (specially Actinedida and Acaridida) and Collembola(Poduromorpha) were predominant in the fauna associated with dung.The colonization of dung begins with the arrival of Collembola, then by Acari, and finally by the rest ofmesofauna. The half-life of dung (L5o), considering the weight decrease, it is of 504 days.